Retrieving Model for Design Patterns - Sarun Intakosum; Weenawadee Muangon (My University, 1970)
The purpose of this research is to develop a retrieving model for design patterns, based on problem domain context. The research aims to provide a convenient way for developers to access to the right design patterns that can solve their design problems. The proposed model is composed of two major parts, the analysis of design pattern documents to create searchindexes, and the calculation of index weight. Vector space model is used to calculate similarity between queries and documents. The result of this research shows that precision of the proposed model, in retrieving correct design patterns, is about 70 percents in average.
Keywords: Similarity (geometry); Design pattern; Vector space model; Software design pattern; Software Engineering Research